Volatilização de amônia de adubos nitrogenados sob diversas condições ambientais na cultura do milho - Marcondes, Angela Lemos Prestes (2007)
Experiments in laboratory and house of vegetation with two ground, one of arenaceous texture (PVAd) and another argillaceous one had been developed (NVdf), beyond a study the field, having for objective to evaluate the agronomic effectiveness of the nitrogen fertilization, evaluating losses of N for volatilization of different nitrogen seasonings: urea; urea + oil; urea + inhibiting of urease; urea + sulphate of ammonium and ammonium sulphate, applied in covering and superficially, the culture of the maize. In the study in laboratory, the determination of the volatilized N was carried through hermetically closed cylindrical bottles with use of collectors in two periods of evaluations, (3 and 7 days), two ground (arenaceous and argillaceous) and five nitrogen sources. In the study in vegetation house, two ground (arenaceous and argillaceous), six periods of evaluations (1, 2, 3, 4, 7 and 8 days) and five nitrogen sources had been used. One evaluated height of plant, diameter of colm, production of dry biomass and text of total N. In the study the field, had been evaluated the following sources of N in covering: urea, urea absorbed in oil, urea with inhibitor of urease and mixtures of 100 kg of N as urea with increasing doses of ammonium sulphate (0, 10, 20, 30 and 40 kg ha-1 of N). The volatilized amount of N-NH3 was measured by means of ammonia collectors installed in the two lines central offices of each parcel in 3? and 7? day after fertilization. Total N in the fabric foliar and the grains, mass of 1000 grains and productivity was determined. In the study in laboratory and house of vegetation, the texture of the ground was verified that, as well as its CTC and amount of organic substance, had influenced the losses for volatilization of N-NH3, being bigger in the ground arenaceous (PVAd) of that in the ground argillaceous (NVdf) and with urea application in both the places, while that the imbibitions of the urea in oil did not imply in reduction of the loss of NNH3. The mixture urea (100 kg ha-1 of N) + ammonium sulphate (40 kg ha-1 of N) contributed for reduction of the losses of N-NH3, in average, of 8% in the evaluation lead in laboratory and 5% in the experiment in house of vegetation in comparison with the urea in the average of ground. The urea fertilization with inhibitor of urease presented minors losses and provided to one better exploitation of the N. In the study the field, the volatilization of ammonia occurred until 7? day after application of the treatments, being the total losses of the source urea of 13% and 4% in the urea with inhibitor of urease. The dose of ammonium sulphate in mixture with urea that implied in lesser loss of N-NH3 was of 9 kg ha-1 of N. Divide to low the rain availability, did not have significant difference of seasonings nitrogen in the maize productivity, but the urea fertilization with inhibitor of urease more provided to an increment of 377 kg in comparison the urea